Nutritional Burden in Tuberculosis and Inter-sectoral Nutritional Management for Tuberculosis Patients in Malaysia - Khalid Mokti; Zaleha Isa; Mohd Rizal Abdul Manaf; Firdaus Hayati; Syed Sharizman Syed Abd Rahim (2020)
Undernutrition and tuberculosis (TB) are a vital issue in most developing countries of the world. Both of these medical problems tend to have interacted with each other and bidirectional. The undernutrition creates a more significant problem in patients with active TB rather than among healthy individuals. Despite that, there is no protocol available on nutritional support in Malaysia to tackle on this issue. The objective of this review is to explore the nutrition burden of TB disease and the management available in Malaysia. The treatment for TB lasts for six months and above. Hence, it causes a financial burden not only for the healthcare provider but for the patient and the family members. If treatment is not successful and extends to a few months, it will increase the cost of the treatment. Malnutrition in TB patients will cause a problem in the outcome of TB treatment. It includes worsening of the disease, delayed sputum conversion, and increased risk of mortality. Other problems include malabsorption of Rifampicin, drug-induced hepatotoxicity, increased rate of relapse, and persistent of positive cultures in MDR-TB. Benefits of nutritional support for tuberculosis patients include improved body weight, increase in adherence/compliance to the tuberculosis treatment and increase in the success of the treatment. Implementation of nutritional support protocol by the government and Non-profit organization (NGO) will be beneficial and improve the quality of life of tuberculosis patients.